1995
DOI: 10.1111/j.1600-0714.1995.tb01197.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrin receptors and their relationship to cellular proliferation and differentiation of oral squamous cell carcinoma. A quantitative immunohistochemical study

Abstract: The expression of extracellular matrix (ECM) proteins (fibronectin, laminin, collagen IV) and ECM receptors of integrin type (alpha 2 beta 1, collagen receptor; alpha 6 chain of the fibronectin receptor; alpha 6 chain of the laminin receptor) were examined in normal oral squamous epithelium and in invasive areas of squamous cell carcinomas with various differentiation and proliferation activities (Ki-67 antigen labelling), evaluating the presence, quantity (using an image analysis system) and distribution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
3
11
1
4
Order By: Relevance
“…These cells are characterized by well-established differentiation, a fact explaining the high expression of ␣ 5 ␤ 1 integrin. However, these results disagree with the findings of Kosmehl et al, 18 who observed discontinuous staining for ␣ 5 ␤ 1 integrin at the epithelial-basement membrane interface in normal oral mucosa and a more intense staining in poorly differentiated epidermoid carcinoma. According to these authors, expression of ␣ 5 ␤ 1 integrin tended to be higher in more undifferentiated cells.…”
Section: Discussioncontrasting
confidence: 99%
“…These cells are characterized by well-established differentiation, a fact explaining the high expression of ␣ 5 ␤ 1 integrin. However, these results disagree with the findings of Kosmehl et al, 18 who observed discontinuous staining for ␣ 5 ␤ 1 integrin at the epithelial-basement membrane interface in normal oral mucosa and a more intense staining in poorly differentiated epidermoid carcinoma. According to these authors, expression of ␣ 5 ␤ 1 integrin tended to be higher in more undifferentiated cells.…”
Section: Discussioncontrasting
confidence: 99%
“…In dysplasia and carcinoma BM structural irregularities, including reduplication, splitting, attenuation and breaks (Ueno et al, 1997) have been well documented by electron microscopy. Moreover, immunohistochemical BM defects and a loss of corresponding integrins in head and neck squamous cell carcinomas have been reported (Downer et al, 1993;Harada et al, 1994;Kobayashi et al, 1995;Kosmehl et al, 1995aKosmehl et al, , 1996. In this study, multifocal breaks of BM continuity were observed in the invasion zone of all carcinomas, regardless of the laminin chain specificity of the antibodies.…”
Section: Structural Basement Membrane Alterations In Oscc Demonstratementioning
confidence: 59%
“…The integrins also reflect the differentiation status of tumor cells [31][32][33] and are considered to be involved in the interaction of tumor cells with ECMs. 34 Immunohistochemical staining for specific cytokeratins has been used to categorize OSCC in accordance with differentiation status.…”
Section: Discussionmentioning
confidence: 99%